2023
DOI: 10.1037/qup0000248
|View full text |Cite
|
Sign up to set email alerts
|

Systems and selves: An exploratory examination of dissociative identity disorder on TikTok.

Abstract: In 2020, in the midst of COVID-19 related social distancing, the relatively new social media platform, TikTok, burgeoned in popularity. One somewhat surprising topic area that rose to prominence on the platform during this time was dissociative identity disorder (DID). Some researchers and clinicians expressed concern that the proliferation of DID content on the platform may have contributed to a marked increase in individuals presenting with DID and related symptoms. However, given that the relationship betwe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 51 publications
0
1
0
Order By: Relevance
“…Among these is the spread of mis/information about mental health and a variety of mental illnesses [ 10 , 12 , 13 ]. Research has suggested this mis/information spread on sites like TikTok has coincided with a rise in young social media users identifying with a variety of mental health concerns, including less prevalent disorders like Dissociative Identity Disorder and Tourettes [ 14 17 ]. Even more noxious impacts of social media use—including psychic distress, anxiety, depression, body image disturbance, self-injurious behavior, and suicidality—have also been found in a number of studies [ 3 , 18 20 ].…”
Section: Introductionmentioning
confidence: 99%
“…Among these is the spread of mis/information about mental health and a variety of mental illnesses [ 10 , 12 , 13 ]. Research has suggested this mis/information spread on sites like TikTok has coincided with a rise in young social media users identifying with a variety of mental health concerns, including less prevalent disorders like Dissociative Identity Disorder and Tourettes [ 14 17 ]. Even more noxious impacts of social media use—including psychic distress, anxiety, depression, body image disturbance, self-injurious behavior, and suicidality—have also been found in a number of studies [ 3 , 18 20 ].…”
Section: Introductionmentioning
confidence: 99%